Das neue Volk Gottes in Hispanien Die Bibel in der christlich-iberischen Historiographie vom 8. bis zum 12. Jahrhundert - Marschner, Patrick Sebastian (LIT Verlag GmbH & Co. KG, 2023)
This book investigates for the first time the role of the Bible in the Christian-Iberian chronicles from 8th to 12th centuries against the background of of the Arab/Berber foreign rule over major parts of the medieval Iberian Pensinula. The depiction of the Christian chronicler's own history in the period investigated offers an immense amount of biblical motifs. Historical protagonists, peoples and specific groups among these peoples, the contemporary common model of history as well as the idea of salvation are depicted as fulfilment of biblical pre-announcements, resulting in the role allocation of the 'Self' and the 'Other' in salvific history.